Coconut Tree (Cocos nucifera) Products: A Review of Global Cultivation and its Benefits - Henrietta, H. Mary; Kalaiyarasi, K.; Raj, A. Stanley (Journal of Sustainability and Environmental Management, 2022)
The coconut tree (Cocos nucifera) is one of the most extensively and widely used palm trees. The coconut palm is regarded as the "tree of life," or "Kalpavriksha." Humans have been cultivating a wide range of coconut trees around the world. This study is based on analysis of secondary data on cultivation of coconut trees and its benefits. Due to increased insect infestations and a changing habitat, the lifespan of coconut trees have been affected. Coconut product market has become the fastest expanding business due to the anti-viral compounds found in it. The coconut is used to produce oils, even the shells used for craft materials. People have been using coconut trees to make brooms and woods are being used to make furniture, construction materials for dwellings, and hardwood floors. It shows the livelihood of people around the world have been changed due to the cultivation of coconut trees. Indonesia, India and Philippines are top three countries to be economically benefitted from the plantation of coconut trees. As there is high demand of coconut based products worldwide, farmers need to be made aware about this economic value for increment in production.